Emerging PBL Futures: Exploring Normative Scenario Development as an apporach to support Transformation in Problem-based Learning and Higher Education - Lykke Brogaard Bertel; Anette Kolmos; Anders Melbye Boelt (Journal of Problem Based Learning in Higher Education, 2021)
Problem-based learning has a long history of transforming higher education institutions at course-, curriculum- and even systemic levels, and has shown to enhance student-centered learning and core pedagogical values such as facilitating collaboration, complex problem-solving skills and critical thinking. However, rapid digitalisation in higher education and emerging trends such as personalised life-long learning through micro-credentials and flexible curriculum models challenges existing, traditional onsite PBL practices and require new frameworks for envisioning future practice in higher education based on an understanding of its local context and the inclusion of multiple relevant stakeholders and practitioners, not only to co-create potential scenarios suitable for a particular educational institution but also in pointing to directions for initiating and maintaining this change process on a systemic level. In this paper, we propose normative scenario thinking as a method for educational development, and present the first steps and initial findings from a process of normative scenario development within a PBL university. The aim of this process has been to identify and explore key trends and core values that inform the development of future scenarios for the conceptualisation and implementation of PBL at the university, in a digital age. Through the analysis of a specific scenario related to project variation and reflection, we exemplify how a value-based and problem-oriented approach to exploring emerging PBL futures can facilitate systemic change in higher education.